Audit on the management of infants with maternal Hepatitis C (HCV) infection at a neonatal abstinence (NAS) follow-up clinic. (7th June 2011) - Vasudevan, C; Thomas, A; Vithlani, R
Abstract : Infants of Hepatitis C virus (HCV) positive women have a 5% risk of infection and require screening according to the 2008 HCV protocol. Children of drug users have poor health attendance rates. The neonatal abstinence (NAS) follow-up clinic provides a service to infants born to substance and alcohol using mothers. This audit aimed to establish whether children born to HCV infected mothers referred to the NAS clinic from January to December 2007 were screened according to the protocol. Results: 83 children were referred to the NAS Clinic, 12 mothers declined or were not offered HCV antenatal screening. 51/71(72%) were HCV antibody negative. 20/71 (28%) were HCV antibody positive of whom 8 were HCV RNA PCR positive. 18/20 (90%) of the infants were screened and all were HCV antibody negative at final testing. One child has not been screened due to persistent non-attendance and liaison by the specialist nurse and social care has enabled the child to be booked for future testing. Conclusion: 28% of mothers were HCV antibody. None of the children screened were found to be positive for HCV infection. More than 50% of the children of confirmed HCV positive mothers did not have tests carried out in time strict adherence to protocol was difficult due to chaotic nature of client group and poor clinic attendance. The current infant screening protocol should be reviewed to consider whether screening infants of HCV antibody positive, PCR negative mothers is justified given that this probably reflects past infection and low risk to the infant.